2009
DOI: 10.1021/cm901726s
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of TiSi Nanowires on C54 TiSi2 Thin Film: An Amorphous Titanium Silicide Interlayer Assisted Nanowire Growth

Abstract: A C54-TiSi2 film was grown on a Si substrate at 1073 K by low pressure chemical vapor deposition (LPCVD) employing titanium subchlorides TiCl x(g), generated by reacting between TiCl4(g) and Ti(s) at 1173 K, as the Ti source. Growth of titanium silicide (TiSi) nanowires (NWs; diameter 30−80 nm, length several micrometers) on a C54-TiSi2 film was observed. Growth direction of the NWs was determined to be along the [010] axis. An amorphous titanium silicide interlayer was observed between the NWs and the C54-TiS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
0
10
1
Order By: Relevance
“…Our measured low residual resistivity ratios ρ (300 K)/ ρ 0 <2 strongly suggest the presence of large amounts of defects (e.g., point defects) in the NWs, where ρ 0 is the residual resistivity due to elastic electron scattering off defects. This observation is in sharp contrast to the conclusion drawn from HRTEM and XRD studies [5], where structure characterizations indicated good crystalline structures without noticeable lattice defects. Indeed, the electrical transport measurement is one of the most sensitive techniques for probing defects in single nanoscale structures [17-19].…”
Section: Resultscontrasting
confidence: 99%
See 4 more Smart Citations
“…Our measured low residual resistivity ratios ρ (300 K)/ ρ 0 <2 strongly suggest the presence of large amounts of defects (e.g., point defects) in the NWs, where ρ 0 is the residual resistivity due to elastic electron scattering off defects. This observation is in sharp contrast to the conclusion drawn from HRTEM and XRD studies [5], where structure characterizations indicated good crystalline structures without noticeable lattice defects. Indeed, the electrical transport measurement is one of the most sensitive techniques for probing defects in single nanoscale structures [17-19].…”
Section: Resultscontrasting
confidence: 99%
“…Our TiSi NWs were synthesized via a low-pressure chemical vapor deposition process using TiCl 4 and titanium powder as precursors; no templates or catalysts were needed [5]. The growth mechanism and detailed structure and composition characterizations by high-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), and other techniques have been reported by Lin et al in [5].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations